(untitled) (Eurasian Research Bulletin, 2023)
This scientific article explores the use of modern technologies for the restoration of degraded desert and pasture ecosystems. Degradation of these environments is a global concern, resulting from human activities and climate change. The study reviews relevant literature, analyzes existing methodologies, and presents innovative approaches to restore and rehabilitate desert and pasture lands. The article highlights the potential of modern technologies, such as remote sensing, artificial intelligence, and precision agriculture, in promoting sustainable restoration practices. The findings emphasize the significance of adopting these technologies to achieve successful restoration efforts and mitigate the impacts of desertification and land degradation on biodiversity and food security